2011
DOI: 10.1093/glycob/cwr081
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of two distinct polysialic acids, α2,8- and α2,9-linked polymers of N-acetylneuraminic acid, in distinct glycoproteins and glycolipids in sea urchin sperm

Abstract: Naturally occurring polysialic acid (polySia) structures have a large diversity, primarily arising from the diversity in the sialic acid components as well as in the intersialyl linkages. In 2004, we demonstrated the presence of a new type of polySia, 8-O-sulfated N-acetylneuraminic acid (Neu5Ac) capped α2,9-linked polyNeu5Ac, on the O-glycans of a major 40-80 kDa sialoglycoprotein, flagellasialin, in sea urchin sperm. In this study, we demonstrated that another type of polySia, the α2,8-linked polyNeu5Ac, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The evolutionary position of Ophiuroidea, with some 2000 living species (4), makes this class of organisms an interesting target to study the phylogeny of protein-linked glycans of not only echinoderms but also of vertebrates. To date, a major focus of glycostructural studies of echinoderms has been their O-glycans and glycolipids as well as some proteoglycan-like polymers involved in species-specific induction of the acrosome reaction during fertilization (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). From these studies, it appears that, in contrast to protostomes, sialic acids are probably a frequent component of echinoderm glycoconjugates and, compared with "higher" vertebrates, occur also in sulfated and methylated forms (16).…”
mentioning
confidence: 99%
“…The evolutionary position of Ophiuroidea, with some 2000 living species (4), makes this class of organisms an interesting target to study the phylogeny of protein-linked glycans of not only echinoderms but also of vertebrates. To date, a major focus of glycostructural studies of echinoderms has been their O-glycans and glycolipids as well as some proteoglycan-like polymers involved in species-specific induction of the acrosome reaction during fertilization (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). From these studies, it appears that, in contrast to protostomes, sialic acids are probably a frequent component of echinoderm glycoconjugates and, compared with "higher" vertebrates, occur also in sulfated and methylated forms (16).…”
mentioning
confidence: 99%
“…It was highly sulfated but differed from a similar molecule found in the egg jelly due to the occurrence of Neu5Ac instead of Neu5Glc and also due to very low proportion of other constituent sugars (Table 1). The sialic acid-rich polysaccharide from the sperm head had similarity with another glycoconjugate, named flagellasialin, which also contained Neu5Ac (Miyata et al 2006(Miyata et al , 2011. Studies on whether the sialic acid-rich molecule found in the sperm head interacted with the sulfated fucan from the egg jelly followed the analogy of the interaction of sulfated polysaccharides that regulated sponge cell-cell adhesion (Vilanova et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of flagellasialin in the motility of sea urchin sperm through the intracellular calcium ion regulation has been reported (Kambara et al 2011). The presence of α-2→8-linked di-, tri-, tetra and polyNeu5Ac unique gangliosides has also been documented in these cells (Ijuin et al 1996;Miyata et al 2011). Most sialic acids on the vertebrate cell surface participate in recognition and interaction events during the growth, development and immune response (Nasirikenari et al 2006;Nacher et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of diSia on the glycolipids (GD3 and GT1b) have been well studied, while far less knowledge about the functions of diSia and oligoSia on the glycoproteins has been reported [55][56][57]. Interestingly, oligoSia and polySia with the degree of polymerization up to 16 have been recently found in glycolipids of sea urchin sperm [58], although their functions remain to be elucidated.…”
Section: Di- Oligo- and Polysialic Acids (Disia/oligosia/polysia)mentioning
confidence: 99%